Edukasi Akhlaqul Karimah Dalam Menuntut Ilmu Bagi Santri PP. Bahrul Ulum Klampisan Kandangan Kediri Menggunakan Kitab Ta’llim Muta’alim - Nila Mufidatu M; Fadhila Sidiq Permana (LP3M IAIFA Kediri, 2021)
This report discusses the learning of akhlaqul karimah in the guise of pesantren bahrul ulum, this study is motivated by the importance of understanding akhlaq because the problem is very concerned with the behavior that must be owned by a student (someone who seeks knowledge) but not all students understand about the material. This researcher aims to answer the problem: How is the understanding of ahklaq that must be owned by a santri both men and women students in seeking knowledge. Data is obtained through observation, practice, and interviews. The approach used in this study is the phenomenological approach, and all data is analyzed using descriptive analysis. This study used the PAR method. Participatory Action Research is one of the research models that look for something to connect the research process into the process of social change. The purpose of this research is to increase the knowledge of a student of Pondok Pesantren Bahrul Ulum Kelampisan, Kandangan, Kediri. both sons and daughters against ahklaqul karimah in studying.